Kemampuan Senyawa Bioaktif Formula Salep Ekstrak Metanol Curcuma aeruginosa Roxb Dalam menghambat Pertumbuhan Staphylococcus aureus Menggunakan Media Nutrient Agar - Sabda Wahab; Syaiful Bachri; A. Fitra Nugraha; Irman Idrus (JSSHA ADPERTISI JOURNAL, 2021)
Curcuma aeruginosa Roxb contains essential oils, tannins, curcumol, curcumenol, iso curcumenol, kurzerenone, kurdion, curcumalactone, germacron, a,b,g-elements, linderazulene, curcumin, demethyoxy-kurcumin, bisdemethyoxy blood release and dirty after childbirth, skin diseases such as scabies, rashes and ulcers, heartburn (colic), mouth sores, coughing, shortness of breath, and intestinal worms. Staphylococcus aureus can cause diseases such as infection of the hair follicles and sweat glands, ulcers, and infection in wounds. Research purposes : This study aims to determine the inhibitory ability of Curcuma aeruginosa Roxb to the growth of Staphylococcus aureus. Research result : By applying the diffusion method at an incubation period of 1 x 24 hours at 37oC, Formula I (5%) obtained an inhibitory value of 12.7 mm, 10% (16.3 mm), 15% (21.3 mm), negative control (0 mm), and positive control (25.3 mm). Conclusion :The formula of Curcuma aeruginosa Roxb ointment has the ability to inhibit taphylococcus aureus. Analysis of Variance (ANOVA) shows value (significant). Newman-Keuls analysis for all concentrations also obtained significant results